PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA BERBASIS DISCOVERY LEARNING PADA MATERI TEOREMA PYTHAGORAS KELAS VIII MTsN LUBUK BUAYA PADANG - Ramadanti, Doni Sri (STKIP PGRI Sumbar, 2014)
Teaching materials is an important part of learning because it can be used as alearning resource for teachers and students. Teaching materials which areexpected to be able to guide students to learn independently, easy to understandstudents, communicative language with students and improve students problemsolving abilities. Existing textbooks have not been able to guide students to aconcept and solve mathematical problems. Therefore, developed teachingmaterials in the form of students worksheet based on discovery learning ofpythagorean theorem materials. Type of research is the development of the 4-Dmodel. Based on the results of testing the validity of the students worksheet-basedvalidator problem by showing that a students worksheet based on the criteria validissue, namely 4,00. Practicalities of test results by teachers and students indicatethat the lkse is based on the category of very practical problems, namely 90,25%for students while 85% for teachers.